Lessons from the Case of Jahi McMath - Truog, Robert D. (The Hastings Center report, 2018)
Jahi McMath's case has raised challenging uncertainties about one of the most profound existential questions that we can ask: how do we know whether someone is alive or dead? The case is striking in at least two ways. First, how can it be that a person diagnosed as dead by qualified physicians continued to live, at least in a biological sense, more than four years after a death certificate was issued? Second, the diagnosis of brain death has been considered irreversible; in fact, there has never been a case of a person correctly diagnosed as brain-dead who improved to the point that the person no longer fulfilled the diagnostic criteria. If the neurologist Alan Shewmon is correct that, prior to her cardiac arrest in June 2018, McMath no longer met the criteria for brain death and was actually in a minimally conscious state, this case could have momentous implications for how we think about this diagnosis going forward. In this essay, I will offer a hypothesis that could, perhaps, explain both these aspects of the case. The hypothesis is based on differences in how we distinguish between biological and legal categories. The law tends to prefer to draw bright-line distinctions between categories, whereas biological categories tend to fall along a spectrum, without sharp distinctions.